Environment-friendly and chromium-free passivation of copper and its alloys. (December 2021) - Yang, Tao; Chen, Wenge; Li, Xin; Song, Jiulong; Dong, Longlong; Fu, YongQing
Abstract: Benzotriazole (BTA) and tolyltriazole (TTA) were used to passivate pure copper and chromium bronze alloys for environmental protection. Using the chemical immersion treatment, a dense film of chromium-free passivation layer was formed on surfaces of both the pure copper and chromium bronze alloys. Microstructure, crystalline phases and chemical bonds of the passivation layers were systematically characterized, and the passivation mechanisms were studied. The passivation layer was mainly consisted of CuO, Cu2 O, polymers of Cu-BTA-TTA and Cu(I)BTA-TTA. The formation mechanism of the chromium-free passivation layer was identified as combined oxidation and adsorption, and the main passivation processes included oxidation and dissolution of the matrix, adsorption of BTA and its derivatives, self-stabilization process of the adsorbed film, and filling of passivation film's voids by oxide particles. Graphical Abstract: ga1